VETO sprzeciw twórców muzyki hip-hopowej wobec sytemu polityczno-gospodarczego Polski postkomunistycznej - Fecko, Daniel (My University, 2014)
Praca pod tytułem „VETO sprzeciw twórców muzyki hip-hopowej wobec sytemu polityczno-gospodarczego Polski postkomunistycznej” rozprawia o subkulturze hip-hop w Polsce. Subkultura ta powstała w wyniku problemów społecznych, które dotknęły Polaków po upadku komunizmu. Teksty utworów hip-hopowych przejawiają bunt wobec państwa, bezrobocia i biedy. Hip-hop to zatem sprzeciw wobec systemu polityczno-gospodarczego.

Work under title „VETO objections framers of music hip-hop against system politically -economic post-communist of Poland” discourse about subculture hip-hop in Poland. This subculture is the result of social problems, that hit the Poles after the fall of communism. Hip-hop lyricsdisplay of rebellion against the State, joblessness and poverty. Hip-hop is, therefore, opposition to the political and economic system.
VETO objections framers of music hip-hop against system politically -economic post-communist of Poland
Keywords: hip-hop; problemy społeczne; transformacja systemowa; bunt młodzieży; Youth subculture; hip-hop; social problems; system transformation; subkultura młodzieżowa; riot of young people